Navigating the Journey: A Phenomenological Exploration of Graduate Students’ Experiences in Scientific Article Writing - Fitri Yuliana; Sulis Triyono; Ashadi Ashadi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Writing scientific articles presents considerable challenges for many graduate students, often due to insufficient support and resources. As academic publishing is crucial for scholarly development, understanding the obstacles students face is essential for providing effective interventions. This qualitative study employed a phenomenological approach to explore the experiences of ten graduate students from diverse academic disciplines and semesters. Data were collected using semi-structured interviews, preceded by an e-reflection exercise completed by each participant. Interpretative Phenomenological Analysis (IPA) was used to examine the data, following steps such as identifying significant themes, interpreting their meaning, and synthesizing the findings. The analysis revealed three primary challenges in scientific writing: difficulty selecting a topic, poor time management, and limited academic writing proficiency. To overcome these issues, students engaged in peer discussions, developed task lists, and participated in scientific writing training programs. These findings highlight the need for structured writing support within graduate programs. Institutions should consider implementing targeted interventions, such as peer writing groups and academic writing workshops, to enhance students’ writing competence and confidence. Graduate students encounter multifaceted challenges in scientific article writing. However, through collaborative strategies and institutional support, these obstacles can be effectively mitigated. Future research should further investigate scalable academic writing interventions to support student success.